GESTATIONAL SYPHILIS: REPERCUSSIONS FOR POSTPARTUM WOMEN - Jéssica Gama da Silva; Giovana Calcagno Gomes; Juliane Portella Ribeiro; Bianca Contreira de Jung; Pâmela Kath de Oliveira Nörberg; Marina Soares Mota (Universidade Federal do Paraná, 2019)
Objective: To know the repercussions of the diagnosis of Gestational Syphilis for the postpartum woman. Method: A qualitative research carried out in a pediatric unit of a university hospital in southern Brazil. 15 postpartum women participated of children admitted to the sector diagnosed with congenital syphilis. Data was collected by semi-structured interviews in the first half of 2018 and submitted to content analysis. Results: Data was obtained about the receipt of the diagnosis, the reactions regarding the diagnosis, the influence of the diagnosis during pregnancy and childbirth and the treatment of gestational syphilis. Conclusion: Misinformation of the puerperal women regarding syphilis infection, especially regarding care to avoid transmission and reinfection. We highlight the educational role of nurses with these women in the pursuit of reducing (re)infections by syphilis.